Enamel chipping and its ecological correlates in African papionins: Implications for hominin feeding behavior. Issue 177 (April 2023) - Fannin, Luke D.; Swedell, Larissa; McGraw, W. Scott
Abstract: African papionins are classic paleoecological referents for fossil hominins. Enamel chips on the teeth of baboons and hominins are argued to represent responses to similar dietary habits; however, a comprehensive analysis of modern papionin chipping is lacking, leaving open the question of analog suitability. Here, we investigate patterns of antemortem enamel chipping across a diverse set of African papionin species occupying a range of ecological niches. We compare papionin chipping frequencies to estimates for Plio-Pleistocene hominins to address hypotheses of habitat and/or dietary similarities. Antemortem chips in seven African papionin species were scored on intact postcanine teeth (P3–M3) using established protocols. Chip size was scored on a tripartite scale. Papio hamadryas and Papio ursinus —two common paleoecological referents—display higher levels of chipping than Plio-Pleistocene hominin taxa ( Australopithecus and Paranthropus ) posited to have similar dietary habits. Papio populations occupying dry or highly seasonal habitats accumulate more large chips than Papio taxa occupying more mesic habitats, and terrestrial papionins chip their teeth more often than closely related taxa occupying arboreal niches. Chipping is present on the teeth of all Plio-Pleistocene hominins; however, chipping in baboons ( P. ursinus and P. hamadryas ) consistently exceeds most hominin taxa. Chipping frequencies on their own do not reliably sort taxa into major dietary groupings. We conclude that the large differences in chipping frequency may instead reflect habitat use and food processing idiosyncrasies. Less chipping in Plio-Pleistocene hominin teeth compared to modern Papio is more likely attributable to differences in dental morphology rather than diet.